2005
DOI: 10.1111/j.1439-0418.2005.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of two mitochondrial DNA haplotypes in Japanese populations of Hypera postica (Col., Curculionidae)

Abstract: In Japan, the alfalfa weevil, Hypera postica, was first recorded in 1982 from Fukuoka and Okinawa Prefectures and has been spreading to many other prefectures. The weevil seriously infests the Chinese milk vetch, Astragalus sinicus, one of the most important honey resources for honeybees in Japan. Direct sequencing of partial mitochondrial DNA and PCR-RFLP data for alfalfa weevil individuals indicated the coexistence of two haplotypes at various localities in Japan. Molecular phylogenetic analysis for H. posti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 18 publications
2
28
0
2
Order By: Relevance
“…Throughout the Japanese archipelago, no Eastern strain has been reported to date (Kuwata et al . ). Recently, we found that the Japanese Western strain from Fukuoka populations in northern Kyushu was uninfected with Wolbachia (Iwase et al .…”
Section: Collected Populations Of Hypera Postica For Eastern‐strain Hmentioning
confidence: 97%
See 1 more Smart Citation
“…Throughout the Japanese archipelago, no Eastern strain has been reported to date (Kuwata et al . ). Recently, we found that the Japanese Western strain from Fukuoka populations in northern Kyushu was uninfected with Wolbachia (Iwase et al .…”
Section: Collected Populations Of Hypera Postica For Eastern‐strain Hmentioning
confidence: 97%
“…Hypera postica has become a serious pest in the apiculture industry (Okumura ; Kuwata et al . ), reaching higher densities on A. sinicus than on other host plants (Iwase et al . ).…”
Section: Collected Populations Of Hypera Postica For Eastern‐strain Hmentioning
confidence: 99%
“…In less than a century after its introduction in America (Titus, 1909), populations have diverged and a detectable hybrid zone between lineages has been established (Hsaio, 1996;Bundy et al, 2005). Differences between alfalfa weevil populations have been detected for molecular (Hsiao, 1993;Kuwata et al, 2005;Böttger et al, 2013), morphological (Pienkowski et al, 1969;Bland, 1984), and ecological aspects (Armbrust et al, 1969;Davis, 1970;Hsiao and Hsiao, 1985;Skuhrovec et al, 2014). Some of the ecological variation that was observed in the American alfalfa weevil lineage was related to life history traits; for example, the location of pupae differed with some populations having pupae located on the ground and others located on plants (Bundy et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…After the first introduction to America, three strains were identified (Bundy et al 2005;Hsiao 1993) which show slightly morphological differences (Bland 1984;Pienkowski et al 1969), but high ecological differences (Bundy et al 2005;Goosey 2009;Hsaio 1996;Hsiao and Hsiao 1985). Further, molecular analysis suggested significant differences between H. postica populations (Bött-ger et al 2013;Erney et al 1996;Kuwata et al 2005). This prior knowledge on population variability of the species in the USA and Japan suggests that it is important to investigate additional populations of H. postica, especially in its native range.…”
Section: Introductionmentioning
confidence: 96%
“…Even though classic morphological analyses are still regarded a powerful tool to distinguish taxa and sometimes even intraspecific populations, traditional morphological analyses have failed in the past to distinguish American populations of the alfalfa weevil (Bland 1984;Erney et al 1996;Kuwata et al 2005;Pienkowski et al 1969). Classic morphological analyses are often limited to few measurements; however, the development of geometric morphometrics, along the advances in statistical methods, provides a powerful tool to study the shape variation of animal populations (Adams et al 2004;Viscosi and Cardini 2011).…”
Section: Introductionmentioning
confidence: 98%